2017
DOI: 10.1080/2162402x.2017.1285991
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell-derived myeloid and plasmacytoid DC-based vaccines are highly potent inducers of tumor-reactive T cell and NK cell responsesex vivo

Abstract: Because of the potent graft-versus-tumor (GVT) effect, allogeneic stem cell transplantation (alloSCT) can be a curative therapy for hematological malignancies. However, relapse remains the most frequent cause of treatment failure, illustrating the necessity for development of adjuvant post-transplant therapies to boost GVT immunity. Dendritic cell (DC) vaccination is a promising strategy in this respect, in particular, where distinct biologic functions of naturally occurring DC subsets, i.e. myeloid DCs (mDCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Using a malignant glioma mouse model, Dey et al have shown that cDCs induced stronger anti-tumor CD8 T cell responses and better anti-tumor efficacy compared to pDCs [ 64 ]. Using human pDCs and cDC2s differentiated from CD34 + hematopoietic stem cells, it has been reported that BDCA1 + cDC2s are superior in generating antigen-specific CD8 T cell immunity, although pDCs are superior in activating natural killer (NK)cells [ 65 ], suggesting that vaccines that combine both cDC2s and pDCs might achieve better anti-tumor efficacy.…”
Section: Plasmacytoid Dc-based Cancer Vaccinesmentioning
confidence: 99%
“…Using a malignant glioma mouse model, Dey et al have shown that cDCs induced stronger anti-tumor CD8 T cell responses and better anti-tumor efficacy compared to pDCs [ 64 ]. Using human pDCs and cDC2s differentiated from CD34 + hematopoietic stem cells, it has been reported that BDCA1 + cDC2s are superior in generating antigen-specific CD8 T cell immunity, although pDCs are superior in activating natural killer (NK)cells [ 65 ], suggesting that vaccines that combine both cDC2s and pDCs might achieve better anti-tumor efficacy.…”
Section: Plasmacytoid Dc-based Cancer Vaccinesmentioning
confidence: 99%
“…Cord blood CD34 + hematopoietic stem and progenitor cells (HSPC) have been shown to be suitable for the differentiation into functional pDCs in vitro (Blom et al, 2000;Chen et al, 2004;Olivier et al, 2006;Demoulin et al, 2012;Thordardottir et al, 2014) and can yield clinically relevant cell numbers: up to 81 (±20) pDCs per single HSPC (Laustsen et al, 2018). CD34 + stem cells can also be isolated from peripheral blood after mobilization with G-CSF and the generated pDCs can induce Ag-specific activation of autologous CD8 + memory T cells ex vivo (Thordardottir et al, 2017). Although using autologous stem cell-derived pDCs for vaccination is a promising avenue for personalized pDC therapeutics, the HSPC differentiation into pDCs still requires long-term culturing, implying that the field still needs to make several advancements before it has clinical potential.…”
Section: Pdc Vaccination In Humansmentioning
confidence: 99%
“…Another commonly used approach is to produce DCs from CD34+ hematopoietic stem and progenitor cells (HSPCs) ( 21 , 22 ), which have an extensive proliferation capacity to generate antigen presenting cells (APCs) with a primary DC phenotype ( 23 ) and the capacity to induce robust anti-tumor T cell responses. These cells are distinct from moDCs ( 24 – 27 ), and more resemble conventional DC or Langerhans resembling cells ( 28 ) that induce stronger anti-tumor T cell responses compared with moDCs ( 29 ). In the setting of cord blood transplantation after chemotherapy in hematologic malignancies, CD34+ HSPCs can be extracted from 20% of the remaining unit that is not transplanted, and developed into an effective DC vaccine, that can be modified at different stages of the manufacturing process, which will be discussed below.…”
Section: Subsets Eligible For Modificationmentioning
confidence: 99%